Adaptive patterns in the p53 protein sequence of the hypoxia- and cancer-tolerant blind mole rat Spalax. Issue 1 (December 2016) - Domankevich, Vered; Opatowsky, Yarden; Malik, Assaf; Korol, Abraham; Frenkel, Zeev; Manov, Irena; Avivi, Aaron; Shams, Imad
Abstract Background The subterranean blind mole rat, Spalax (genusNannospalax ) endures extreme hypoxic conditions and fluctuations in oxygen levels that threaten DNA integrity. Nevertheless, Spalax is long-lived, does not develop spontaneous cancer, and exhibits an outstanding resistance to carcinogenesis in vivo, as well as anti-cancer capabilities in vitro. We hypothesized that adaptations to similar extreme environmental conditions involve common mechanisms for overcoming stress-induced DNA damage. Therefore, we aimed to identify shared features among species that are adapted to hypoxic stress in the sequence of the tumor-suppressor protein p53, a master regulator of the DNA-damage response (DDR). Results We found that the sequences of p53 transactivation subdomain 2 (TAD2) and tetramerization and regulatory domains (TD and RD) are more similar among hypoxia-tolerant species than expected from phylogeny. Specific positions in these domains composed patterns that are more frequent in hypoxia-tolerant species and have proven to be good predictors of species' classification into stress-related categories. Some of these positions, which are known to be involved in the interactions between p53 and critical DDR proteins, were identified as positively selected. By 3D modeling of p53 interactions with the coactivator p300 and the DNA repair protein RPA70, we demonstrated that, compared to humans, these substitutions potentially reduce the binding of these proteins toSpalax p53. Conclusions We conclude that extreme hypoxic conditions may have led to convergent evolutionary adaptations of the DDR via TAD2 and TD/RD domains of p53.